A Comparative Clinical Study to Evaluate the Effect of Shamana Sweda Followed by Nirgundi Guggulu in Vaatakantaka with Special Reference to Calcaneal Spur Amongst Female Population - Suma Astagimath; S G Chavan; Madhusudan Kulkarni (International Journal of Ayurveda and Pharma Research, 2021)
Vatakantaka is characterized by the pain in the heel region and included in the vatavyadhi by Acharya Sushruta. It is common in about 10% of general population. Women are twice more prevalent than men. Vatakantaka is mainly caused due to vitiation of Vatadosha and continuous pressure on the heel region. It can be co-related with Calcaneal spur. It is more prevalent in female due to life style postures like standing for longer period, wearing high heel shoes. Various treatment measures for the management of Vatakantaka are given in the classics of Ayurveda. Siravyadha,Agnikarma and Eranda taila pana are the main chikitsa of Vatakantaka. Achrya Charaka said Vatakantaka is Sweda sadhya Vyadhi. So in this present study, treatment is given with swedana followed by Shamanoushadhi. Here 40 cases of Vatatakantaka vis- a -vis Calcaneal spur were devided in to two groups and subjected to Dashamula churna pinda sweda and valuka sweda for 7 days, followed by Nirgundi Guggulu for 30 days. Patients showed significant results in subjective and objective parameters. The present clinical study has been registered as a Prospective study in clinical trials registry- India (CTRI). Register number – CTRI/2019/11/022132